Aeroponics enables consistent cutting propagation of kratom (Mitragyna speciosa): impacts of photoperiod, cultivar, and rooting hormone - Zhang, Mengzi; Montanez, Cynthia; Pearson, Brian J.; Li, Yuncong; Chen, Jianjun (Frontiers in Plant Science, 2025)
IntroductionKratom (Mitragyna speciosa) has gained increasing attention for its potential to manage pain and alleviate opioid withdrawal symptoms. Despite growing interest, production practices, including vegetative propagation, remain underexplored. This study compared indoor aeroponics with greenhouse mist systems for rooting kratom cuttings and evaluated the effects of photoperiod, rooting hormone, and cultivar on the rooting success.MethodsIn Study I, stem cuttings collected from ‘MR-Malaysian’ over two seasons, 180 each, were rooted in aeroponic units, 15 cuttings per unit. Twelve aeroponic units were randomly assigned to 10-, 14-, or 24-hour photoperiods in environmentally controlled growth rooms, with four units per room. In parallel, cuttings from the same cultivar were evaluated in a greenhouse mist system across three seasons. In each season, 60 cuttings were rooted in four trays, 15 each. In Study II, cuttings derived from three cultivars (MR-Malaysian, DR-Bumblebee, and Hawaii) were tested simultaneously using the indoor aeroponic and greenhouse mist systems, with or without rooting hormone treatments (5 mg/L IBA and 2.5 mg/L NAA). A series of rooting parameters was collected during the two studies.ResultsA 14-hour photoperiod significantly enhanced root initiation and root growth compared to a 10-hour photoperiod, as indicated by increased root length, area, branching, and biomass. The aeroponic system consistently promoted high rooting percentages (85%-92%) and root growth, whereas the greenhouse mist system exhibited high seasonal variability (7%-98%) and inconsistent rooting success. In Study II, ‘MR-Malaysian’ overall outperformed the others, exhibiting high rooting rates and root growth with a relatively short production cycle, as well as being less susceptible to Fusarium. Hormone application increased the number of roots, but it had minimal effects on other parameters.DiscussionOur results showed that the aeroponic system consistently yielded a significantly higher rooting percentage and better rooting quality compared to the greenhouse mist system across the three cultivars. Such qualities included greater final root number, root dry mass, root length, root area, root volume, and higher numbers of root tips, forks, and crossings. However, the aeroponic system may pose a possibility of spreading pathogens. This study, for the first time, demonstrates that photoperiod, rooting system, and cultivar are crucial factors in rooting kratom cuttings. The aeroponic system represents a new and effective way of propagating kratom cuttings year-round.